Pre-service Teachers' Language Ideologies of Dual Language Bilingual Education Program : A Discourse in Language Education Policy - Nupus, Hayati; Djatmika, Djatmika; Ngadiso, Ngadiso (Universitas Hamzanwadi, 2023)
Dual language bilingual education programs have been applied in Indonesia for a long time, especially in Islamic boarding schools. Drawing to classroom language policy, this paper aims to explore language ideologies of pre-service English teachers in implementation of dual language bilingual education (DLBE) program in the classroom and to what extent do their language ideologies affect their DLBE implementation before and after-class reflection. This article uses an ethnography case study in describing and exploring individual phenomena to find out the natural data from individual daily activity. Interview and observation will be used as a data collection. The participants of this study are four pre-service English teachers represented in different race, native-language and gender categories. The focus use in this study on DLBE when students learn more than one language. Languages are separate and distinct when bilingual speakers are compared to monolingual speakers. Therefore, different language ideologies of pre-service teachers which are influenced by race, gender, and native language will affect the implementation of DLBE itself.